Specific Fertilization Practices Reveal Important Insights into the Complex Interaction Between Microbes and Enzymes in Soils of Different Farming Systems - Maša Pintarič; Ana Štuhec; Eva Tratnik; Tomaž Langerholc (Life)
The interaction of microorganisms and their enzyme activity is one of the key indicators for a comprehensive measurement of soil health. The aim of this study was to determine significant correlations between different soil microorganisms and enzyme activities of β-glucosidase, N-acetyl-glucosaminidase, urease, arylamidase, phosphatase, acid phosphatase, alkaline phosphatase, and arylsulfatase after supplementation with standard fertilizer, spent mushroom substrate and composed fertilizer in soils from conventional–integrated, organic and biodynamic farming. Samples were grouped according to the farming system and fertilization for all seasons. The biodynamic farm was the least affected by the different fertilizations, except for standard fertilization. Standard fertilizer caused negative correlations between the actinomycetes and the arylsulfatase in organic and biodynamic farms. The same fertilization affected the actinomycetes/phosphatase relationship differently, regardless of the basic soil structure. Actinomycetes correlated positively with acid phosphatase and urease in conventional–integrated and biodynamic farms after spent mushroom substrate, respectively. Arylamidase activity in relation to total microorganisms responded to fertilization with standard fertilizer and spent mushroom substrate independently of the basic soil structure. Fertilization can influence the soil microbe/enzyme relationships in different soils. Regardless of the basic soil structure, some of these relationships could be important indicators for further studies.